PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KUALITAS LAYANAN HOTEL - Made Wahyu Adhiputra (Business Management Journal, 2017)
as one of the business engaged in the service has a requirement to ensure the service quality that directly or indirectly affect consumers. “BI”Hotel is always trying to provide the best service quality. This can be realized if the employee provides services earnest. According to the expectancy theory argues that the actions of employees who tend to do because of the  hope that the results will be obtained, the optimal service quality is achieved when employees are committed and feel satisfied with their work. This study aims to determine the direct effect  of significant variables of job satisfaction and organizational commitment to service quality “BI” Hotel. Results showed that job satisfaction is directly significant effect onorganizational commitment, job satisfaction is directly significant effect on theservice quality, organizational commitment directly significant effect on theservice quality. The implications of this study thatthe match between workload and salary is very important to note in order to maintain employee commitment to the company. Job satisfaction will increase employee loyalty to the company and the willingness of employees to provide the best service quality so that consumers feel satisfied.Keywords: job satisfaction, organizational commitment, and service quality.